Pengaruh Konflik Peran, Stress, Dan Dukungan Sosial Terhadap Komitmen Afektif Organisasi Pegawai Wanita (Studi Pada Pegawai Wanita Bank X Banjarmasin) - Dwiyanti, Lestari; Said, Laila Refiana; Dahniar, Dahniar (Universitas Medan Area, 2019)
This study aims to analyze the influence of role conflict and stress on the affective commitment of female employees with social support as a moderating variable in Bank X in Banjarmasin. This type of research is explanatory research with a quantitative approach. Respondents in this study were all female employees of the Bank X in Banjarmasin. The sampling technique used is a saturation sampling technique. Data collection uses a Likert scale scale questionnaire. Data analysis techniques using Partial Least Square (PLS) analysis techniques with SmartPLS 3.0 software. The results of the study concludes that there is a significant negative effect of role conflict on affective commitment and there is a significant negative effect of stress on affective commitment. Other findings indicate that social support is able to act as a moderating variable on the influence of role conflict and stress on organizational affective commitment